Associations between livestock keeping, morbidity, and nutritional status of children and women in low and middle-income countries: A systematic review - Alemu, Taddese; Giang Nguyen; Duncan, Alan J.; Baltenweck, Isabelle; Brown, Fiona; Iannotti, Lora L.; McNeill, Geraldine (Cambridge University Press, 2023)
Livestock keeping can positively influence the nutritional status of populations and households through increased consumption of animal-source foods (ASF) and other indirect pathways, but can also adversely affect health by increasing the risk of diseases. We conducted a systematic review synthesising the current state of knowledge on the associations among livestock keeping, infectious disease and the nutritional status of children under 5 years and women of reproductive age in low- and lower–middle-income countries (LMICs). A comprehensive search of 12 electronic databases and grey literature sources published from 1991 to the end of December 2020 was conducted. Investigations exploring relationships between livestock keeping and risk of infectious disease transmission and nutritional status were selected using pre-defined inclusion criteria. After screening and filtering of 34,402 unique references, 176 references were included in the final synthesis. Most (160/176, 90.1%) of the references included in the final synthesis were from sub-Saharan Africa (SSA) and Asia. About two out of every five (42%) studies reviewed showed that livestock production is associated with improved height-for-age Z scores (HAZ) and weight-for-length/height Z scores (WHZ), while close to a third (30.7%) with improved weight-for-age Z scores (WAZ). Similarly, livestock production showed a positive or neutral relationship with women’s nutritional status in almost all the references that reported on the topic. Conversely, four-fifths (66/81, 79.5%) of the references reporting on infection and morbidity outcomes indicated that livestock keeping is linked to a wide range of infectious disease outcomes, which are spread primarily through water, food and insects. In conclusion, in many LMIC settings, livestock production is associated with better nutritional outcomes but also a higher risk of disease transmission or morbidity among women and children.This review was prospectively registered on PROSPERO 2020 [CRD42020193622]